Energy metabolism during chronic endotoxin infusion in the rat, with special reference to free fatty acid turnover. - Goran, M; Frayn, K; Little, R (1988)
We have studied various aspects of whole-body energy metabolism during chronic endotoxin infusion in the rat. In particular, we studied free fatty acid kinetics using bolus injections of 14C-palmitate. The general response to 7 days of chronic endotoxin infusion could be divided into an initial 3- to 4-day period of illness with loss of appetite, followed by rapid recovery. Using saline-infused, pair-fed controls, the following observations were made throughout the 7-day period of endotoxin infusion: 1) Plasma free fatty acids, glycerol and 3-hydroxybutyrate concentrations were reduced; 2) plasma glucose concentrations were elevated; 3) free fatty acid production rates were unaffected; 4) metabolic clearance of free fatty acids was unaffected on day 1 but was significantly greater on days 3 and 7; 5) haematocrits and plasma volumes were elevated. The results suggest that the observed changes in circulating free fatty acid concentrations are more likely to be a consequence of haemodynamic alterations than of metabolic alterations.